2‐Methylhopanoids in geographically distinct, arid biological soil crusts are primarily cyanobacterial in origin. Issue 1 (12th December 2021) - Garby, Tamsyn J.; Jordan, Matthew; Timms, Verlaine; Walter, Malcolm R.; Neilan, Brett A.
Summary: Microbial palaeontology is largely reliant on the interpretation of geologically stable biomarkers or molecular fossils. Biomolecules that are both specific to particular groups of organisms and stable on a geological scale are invaluable for tracing the emergence and diversification of lifeforms, particularly in cases where mineral fossils are lacking. 2‐Methylhopanoids and their diagenic product, 2‐methylhopanes, are highly abundant bacterial membrane lipids, recoverable from samples in excess of a billion years old. In this work we used degenerate PCR, targeting 2‐methylhopanoid biosynthesis genes, and sequencing to show that the ability to produce these molecules in arid biological soil crusts from deserts in diverse geographical locations (Utah, USA, and the Pilbara, Australia) is largely confined to cyanobacteria. These data suggest that 2‐methylhopanes can be used as a proxy for cyanobacterial presence within these environments, contributing to our understanding of the emergence of terrestrial life on Earth.